A stability controlling-based approach for designing 1-D variable fractional delay all-pass filters. Issue 6 (5th November 2018) - Zhao, Hui; Li, Shengnan; Yang, Hongyu; Zhou, Quan
Abstract : Purpose: Variable fractional delay filtering is an important technology in signal processing; the research shows that all-pass variable fractional delay (VFD) filters achieve higher design accuracy than FIR VFD filters; therefore, the design, analysis and implementation of all-pass VFD filters are of great importance. Design/methodology/approach: In this paper, a two-stage approach for the design of general 1-D stable VFD all-pass filters is proposed. The method takes the desired group delay range [ N −1, N ], where N is the filter order. Findings: The design algorithm is decomposed into two design stages: first, a set of fixed delay all-pass filters are designed by minimizing a set of objective functions defined in terms of approximating error criterion and filter stability constraint. Then, the design result is determined by fitting each of the fixed delay all-pass filter coefficients as 1-D polynomials. A design example together with its comparisons with those of the recent literature studies is given to justify the effectiveness of the proposed design method. Originality/value: An illustrating design example shows that the method proposed can achieve better filter performances than the existing ones.